Analysis of Project Delays Impact by Cost in The Construction of A Light Brick Factory in Lamongan Using The Earned Value Method - M. Hery Indra Setiawan; Budi Witjaksana; Jaka Purnama (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
A factory is an industrial building that designed for processing raw materials into products, such as Light Weight Brick Factory that produce light weight brick and other products. The construction of a Lightweight Brick Factory plays a significant role in fostering regional economic development. However, the construction process for this factory has faced several issues leading to delays. This study focuses on the delays encountered in the lightweight brick factory construction project in Lamongan, which had a planned completion timeline of 15 weeks and a contract value of IDR 1,835,474,186. By week 10, the project was delayed by -42.73%, followed by delays of -42.66% in week 11, -44.84% in week 12, -48.08% in week 13, -46.18% in week 14, and -44.68% in week 15 compared to the planned schedule. The project cost performance index (CPI) of 1.32 shows that the actual project costs are smaller than budgeted, The primary factor contributing to the delay was attributed to the contractor or vendor, who faced cash flow issues due to other ongoing challenges.